Local Economic Practices in Developing Islamic Financial Products in Indonesia - Andi Syathir Sofyan; Ayu Ruqayyah Yunus; Muslihati Muslihati; Nurfiah Anwar; Emily Nur Saidy (Al-Tijary, 2021)
The culture and geography of a country are the cause of low Islamic financial inclusion and the lack of public knowledge in the Southeast Asian region about the Arabic term on Islamic financial products. Therefore, this study aims to integrate local wisdom and Islamic financial inclusion and realize Islamic -based financial products based on local wisdom. This research is a qualitative descriptive study that is a literature review. The object of the discussion is sourced from research, articles, and reference books related to this topic. The research results are integrating culture with Islamic financial institutions through several efforts, first preaching the Islamic economy with a psychosufistic approach that manifests in the value of Tauhid, humanity, humility, local wisdom and self-transformation to people with low Islamic financial literacy. The second is to strive to create financial products by identifying traditional economic practices throughout Indonesia based on research analyzed by the ‘urf rule. This research has implications for information on the potential market share of Islamic finance in Indonesia and solutions to developing Islamic financial inclusion. The issue of strengthening the market share of Islamic finance in rural areas is still weak. This research study is the first to develop financial products based on local practices in Indonesia.